All in the Family or Public? Law and Appropriative Costs as Determinants of Ownership Structure - Ramon Castillo; Stergios Skaperdas (Center for Economic Studies and ifo Institute (CESifo), 2003)
We examine how the legal protection of outside shareholders and the appropriative costs that they induce influence the incentives for private firms to go public. A higher degree of protection of shareholders can increase the appropriative costs associated with the conflict between managers and shareholders. To counteract this effect the managers/owners increase the share of the firm they retain so that, overall, higher protection of outsiders increases the likelihood of going public. In addition, we examine how the share of funds raised used to finance the firm affects both appropriative costs and the decision to sell.
Keywords: 330